China and international institutions : alternate paths to global power - Lanteigne, Marc (Asian security studies., 2005)
China has shifted its foreign policy from one that avoided engagement in international organizations to one that is now embracing them. These moves present a new challenge to international relations theory. How will the global community be affected by the engagement of this massive global power with international institutions? This new study explores why China has chosen to abandon its previous doctrine of institutional isolation and details how it is currently unable to balance American power unilaterally and details an indirect path to greater power. In addition, it includes.